To the Discussion on the Political and Administrative Status of the Bosporan Kingdom in the 10th-12th Centuries - Valeriy E. Naumenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
A comprehensive analysis of the sources shows that during the 10th-12th centuries Bosporus, or Bosporan Kingdom, was an important strategic point of the Byzantine Empire in the Northern Black Sea. It performed the functions of a transit trade seaside centre on the south of Eastern Europe, the byzantine fortress on the border with the barbarian world, the residence of governor of the theme and archbishop of Bosporus. The article provides an overview of the main events of the political and administrative history of the Bosporus in the studied period. These include the issues of the end of the “Khazar period” in its history, the historical context and geography campaign of Khazar warlord Pesakh (about 935-941), the Old Russian princes Svyatoslav (965) and Vladimir (about 986-987), the revolt of the archon Georgy Tsula (about 1016) in Khazaria, date of establishment and limits of Tmutarakan principality, the theme Bosporus and byzantine katepanikion of Taurica, political and administrative status of the Bosporus in the 12th century.